2020
DOI: 10.3390/genes11101180
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Characteristics of Dystrophin Pseudoexons and Identification of a Novel Pathogenic Intronic Variant in the DMD Gene

Abstract: Pseudoexon (PE) inclusion has been implicated in various dystrophinopathies; however, its splicing characteristics have not been fully investigated. This study aims to analyze the splicing characteristics of dystrophin PEs and compare them with those of dystrophin canonical exons (CEs). Forty-two reported dystrophin PEs were divided into a splice site (ss) group and a splicing regulatory element (SRE) group. Five dystrophin PEs with characteristics of poison exons were identified and categorized as the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…Instead, we collected 133 pseudoexons from literature, experimentally confirmed using patient, mini, or midigene-derived RNA. Notably, similar findings to our results using approaches other than ESRseq tools have been recently reported, in 42 pseudoexons experimentally validated in the DMD gene, showing a smaller density of exonic splicing enhancers (ESEs) together with a higher density of exonic splicing silencers (ESSs) compared to canonical exons, which suggested that the pseudoexons presented a weaker exon profile in terms of SREs [30]. Interestingly, these differences have also been observed between alternative and canonical exons.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Instead, we collected 133 pseudoexons from literature, experimentally confirmed using patient, mini, or midigene-derived RNA. Notably, similar findings to our results using approaches other than ESRseq tools have been recently reported, in 42 pseudoexons experimentally validated in the DMD gene, showing a smaller density of exonic splicing enhancers (ESEs) together with a higher density of exonic splicing silencers (ESSs) compared to canonical exons, which suggested that the pseudoexons presented a weaker exon profile in terms of SREs [30]. Interestingly, these differences have also been observed between alternative and canonical exons.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the arrangement of cis splicing elements in deep intronic regions, especially those corresponding to regulatory elements, would configure sequences with structures similar to those of canonical exons [30,31]. This landscape of regulatory zones would favor the generation of pseudoexons if a new deep intronic variant helps to define these structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMD is one of the largest genes within the human genome, containing 79 protein-coding exons and 42 putative PEs. Importantly, an intronic pathogenic variant of the DMD gene may activate the inclusion of PEs, resulting in disease manifestation ( Xie et al, 2020 ). While PE usage is implicated in dystrophinopathies, the pathophysiology of both myotonic dystrophy type 1 (DM1) and type 2 (DM2) is also associated with the sequestration of Muscleblind-like (MBNL) proteins to RNAs containing CUG or CCUG repeats ( Sznajder and Swanson, 2019 ).…”
Section: Aberrant Pe Regulation Is Implicated In Neurological Disordersmentioning
confidence: 99%
“…PEs have been extensively studied in the context of RBPs, and, in particular, SR proteins, and the presence of pathogenic variants within and around PEs in SR genes and also in functionally unrelated genes has been linked to neurodevelopmental disorders (NDDs) [5]. Finally, the misregulation of PE splicing has also been identified in individuals with Duchenne muscular dystrophy, Ewing sarcoma, and other types of cancer [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%